Checking the Fact-Checkers: Analyzing the Content of Fact-Checking Organizations as Initiatives for Hoax Eradication in Indonesia - Detta Rahmawan; Irma Garnesia; Rudi Hartanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Fact-checking practices are one of the initiatives to combat the spread of hoaxes. An organization called MAFINDO is one of Indonesia's pioneers of fact-checking initiatives. Using content analysis, this research was conducted to examine fact-checked articles published by MAFINDO. We classified the results based on themes, platform, and type of content from July 2015 to July 2020, during the first five years where MAFINDO has been operating. Our study found that, the number of hoaxes being checked increased every year during the period of analysis. Secondly, political themes dominate the entire fact-checking articles verified by MAFINDO. Furthermore, the majority of hoaxes circulated and verified by MAFINDO were predominantly found on Facebook. Finally, hoax mostly found in the form of non-video images and text. This study can be seen as part of the illustrations of the spread of hoaxes in Indonesia and used as a basis for various hoax prevention movements